Lockdown and self-representation: a reading on Instagram’s media diet - Moschin, Massimiliano; Fasoli, Giovanni; Costantini, Carlotta (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
The research addresses content from emerging influencers with the highest engagement rates during the first Italian lockdown of 2020. The objective was to isolate and analyse the posts produced during the crisis in order to assess the media diet of the users of the Instagram social networking platform, detecting the expressive languages of the creators and the nature of the most successful posts according to a sociological and psychological reading to highlight the presence of potential narcissistic traits and their impact on the reputation of the analysed profiles.